2002
DOI: 10.1002/med.10006
|View full text |Cite
|
Sign up to set email alerts
|

Binding interactions between peptides and proteins of the class II Major Histocompatibility Complex

Abstract: The activation of helper T cells by peptides bound to proteins of the class II Major Histocompatibility Complex (MHC II) is pivotal to the initiation of an immune response. The primary functional requirement imposed on MHC II proteins is the ability to efficiently bind thousands of different peptides. Structurally, this is reflected in a unique architecture of binding interactions. The peptide is bound in an extended conformation within a groove on the membrane distal surface of the protein that is lined with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 245 publications
(226 reference statements)
1
83
0
Order By: Relevance
“…This may not be surprising, since the peptides used in this study were ranked according to their binding affinity for the BoLA-DRB3*2703 molecule, alone. Other variables including, peptide degradation, binding affinity for the T-cell receptor, expression of co-stimulatory and adhesion molecules, T-cell receptor avidity, surface density of MHC class II-T-cell receptor complexes, cell-cycle and length of differentiation time have also been demonstrated to influence MHC class II-T-cell receptor mediated T-lymphocyte function [2,6,11,16,20,29,30]. Our initial interpretation of the decreased DNA synthesis in the FMD-VP4 (high binding) peptide-specific T-lymphocytes was that there might be a hole in the T-cell repertoire.…”
Section: Discussionmentioning
confidence: 99%
“…This may not be surprising, since the peptides used in this study were ranked according to their binding affinity for the BoLA-DRB3*2703 molecule, alone. Other variables including, peptide degradation, binding affinity for the T-cell receptor, expression of co-stimulatory and adhesion molecules, T-cell receptor avidity, surface density of MHC class II-T-cell receptor complexes, cell-cycle and length of differentiation time have also been demonstrated to influence MHC class II-T-cell receptor mediated T-lymphocyte function [2,6,11,16,20,29,30]. Our initial interpretation of the decreased DNA synthesis in the FMD-VP4 (high binding) peptide-specific T-lymphocytes was that there might be a hole in the T-cell repertoire.…”
Section: Discussionmentioning
confidence: 99%
“…In live cells, the peptides presented in these complexes derive from intracellular proteins; this complex is the ligand of the antigen receptor of cytotoxic T-lymphocytes. In these molecules, some sub-structures, called peptide-binding specificity pockets, accommodate the side chains of the bound peptides [3][4][5][6][7]. The MHC class II molecules are also tri-molecular complexes, composed of a peptide and two subunits (alpha and beta) that are encoded in the MHC; in the case of the class II molecules, the peptides presented derive from extracellular proteins that are endocytosed in the antigen-presenting cells.…”
Section: Genetic and Functional Variation Of Major Histocompatibilitymentioning
confidence: 99%
“…[12,13] Triggering an efficient immune response to low-molecular-weight compounds 60 (haptens) is an even more challenging task because they are smaller and lack a peptide structure, so they cannot be presented by MHC II molecules unless they are conjugated to proteins prior to immunization. [14,15] One of the emerging strategies for increasing the efficiency of the phagocytosis step, thereby enhancing the antibody response, is the use of nanomaterials that can increase the size of the antigen 65 and modify its surface properties. Micro/nanoparticles (MPs/NPs) have been shown to be well-suited for increasing the immune response against protein and peptide antigens because the dimensions of particulate systems are comparable to those of microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Although nanoparticles increase the size of the immunogen and allow a better uptake by macrophages, only peptide fragments generated after antigen processing can be linked to MHC II molecules on the APCs surfaces. [14] Nevertheless, Maquieira et al [68] have recently reported the existence of a secondary immune response with haptens covalently linked to aluminum oxide nanoparticles, even though further research is probably required to fully clarify the underlying 465 mechanism. On the other hand, the lack of response with the 5 + 3b mixture shows that non-covalent interactions between the positively charged CNT 3b and the negatively charged protein conjugate 5 are not sufficient to preserve the integrity of the immunogen; so, a covalent bond between the CNT and the protein-hapten conjugate is needed for proper antigen delivery inside cells.…”
mentioning
confidence: 99%